2022
DOI: 10.1177/08901171221123053
|View full text |Cite
|
Sign up to set email alerts
|

Where Are All the Men? A Qualitative Review of the Barriers, Facilitators, and Recommendations to Older Male Participation in Health Promotion Interventions

Abstract: Objective Older men have lower participation rates than females in health promotion interventions. We conducted a qualitative review of 20 years of existing research across a variety of academic search databases to outline the barriers, facilitators, and recommendations for this imbalance. Data Source A systematic search was conducted across Google Scholar, PubMed, MEDLINE, CINAHL, Academic Search Premier, Psychology and Behavioral Sciences Collection, and Web of Science from dates January 1, 2000 – December 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The inclusion of psychological, social, and spiritual functioning and the view that these components are interrelated are informative given that previous qualitative research among Black men from rural areas has found that these men mostly associate health with physical health (Abshire et al, 2023). These findings have implications for future health promotion efforts among Black men given that (a) explanations of health among Black men have been narrowly focused (Howell et al, 2023;Jack et al, 2010) and primarily on physical health problems (Gilbert et al, 2016;Wippold et al, 2022) and (b) there have been few comprehensive explanations for the high rates of adverse health among Black men (Griffith et al, 2022;Jack et al, 2010). Future HRQoL promotion efforts among these men may benefit from being comprehensive by addressing physical, psychological, social, and spiritual indicators of health.…”
Section: Discussionmentioning
confidence: 96%
“…The inclusion of psychological, social, and spiritual functioning and the view that these components are interrelated are informative given that previous qualitative research among Black men from rural areas has found that these men mostly associate health with physical health (Abshire et al, 2023). These findings have implications for future health promotion efforts among Black men given that (a) explanations of health among Black men have been narrowly focused (Howell et al, 2023;Jack et al, 2010) and primarily on physical health problems (Gilbert et al, 2016;Wippold et al, 2022) and (b) there have been few comprehensive explanations for the high rates of adverse health among Black men (Griffith et al, 2022;Jack et al, 2010). Future HRQoL promotion efforts among these men may benefit from being comprehensive by addressing physical, psychological, social, and spiritual indicators of health.…”
Section: Discussionmentioning
confidence: 96%
“…This gendered care pattern was also reported in American couples over food-related behavior changes [ 38 ]. Masculine gender roles were identified as a barrier, with husbands paying less attention to their wives’ health promotion activities [ 39 ]. It also may be a manner of protective buffering [ 17 ], such that protecting their spouses from negative emotions and avoiding arguments due to diabetes symptoms or management requirements.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, interventions and strategies to support people to adhere to these dietary recommendations often take a one-size-fits-all approach assuming that such interventions are equally appreciated by men and women and produce equal adherence to recommendations. There is some evidence that points to the contrary, and gender-sensitive policies, treatments and interventions have been called for (33)(34)(35)(36) . In order to design such effective gender-sensitive interventions to promote dietary change, the determinants of dietary intake need to be targeted.…”
Section: Implications For Sex and Gender Analysis In Nutrition Researchmentioning
confidence: 99%